CARBON MANAGEMENT: AN ALTERNATIVE EFFECTIVE AGAINST GLOBAL WARMING? - Vásquez Tarazona, Catya (2011)
Climate change on our planet and Factors That other contaminants, a major cause It Could catastrophe, endangering human existence. From a global perspective, carbon dioxide greenhouse gas is the MOST important today, alters the climate of the Earth. THUS, the problem of global coal Is That balance we all cycle Participate in the coal, whether driving, using electricity produced by fossil fuels (oil, gas), by eating or by the decomposition of the Vast amount of organic matter in the forests Contained Were Destroyed (cutting, burning, etc.).. In That sense, the priority Countries Should Work Together to AIM to Carbon management, ie managing the Global Carbon balance, in order That the concentration of carbon dioxide in the atmosphere is Maintained Levels and safe at our own THUS Avoid self-destruction and Devastating effects on ecosystems. The Idea Is That all actors Economic Become aware of the final balance of carbon dioxide Emissions and Their Impact on global warming, an Environmentally Responsible Behavior Requiring change to Ensure the preservation of the conservation and environment.